2017
DOI: 10.1002/2016jf004047
|View full text |Cite
|
Sign up to set email alerts
|

Ice and firn heterogeneity within Larsen C Ice Shelf from borehole optical televiewing

Abstract: We use borehole optical televiewing (OPTV) to explore the internal structure of Larsen C Ice Shelf (LCIS). We report a suite of five ~90 m long OPTV logs, recording a light‐emitting diode‐illuminated, geometrically correct image of the borehole wall, from the northern and central sectors of LCIS collected during austral spring 2014 and 2015. We use a thresholding‐based technique to estimate the refrozen ice content of the ice column and exploit a recently calibrated density‐luminosity relationship to reveal it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 57 publications
4
32
0
Order By: Relevance
“…The five borehole images are described in detail in Hubbard et al (2016) and Ashmore et al (2017); in summary, across the sites, four different ice types, or units, were identified on the basis of visual appearance, density, and refrozen ice content. Image thresholding was used to determine the proportion of ice within each unit that is composed of refrozen infiltration ice.…”
Section: Introductionmentioning
confidence: 99%
“…The five borehole images are described in detail in Hubbard et al (2016) and Ashmore et al (2017); in summary, across the sites, four different ice types, or units, were identified on the basis of visual appearance, density, and refrozen ice content. Image thresholding was used to determine the proportion of ice within each unit that is composed of refrozen infiltration ice.…”
Section: Introductionmentioning
confidence: 99%
“…We are effectively lumping all changes in the FAC into the surface density, which do not necessarily represent real surface processes. In reality, surface melt is seasonal, and meltwater infiltration and refreezing do not occur right at the surface, resulting in complex ice structures that can be interspersed with firn pockets throughout the vertical firn column (Ashmore et al, 2017). Therefore, in areas of high melt, the scheme will yield unrealistically high surface density estimates in order to accommodate for refreezing within the firn column that is not accounted for in our dry snow densification model.…”
Section: Ground-penetrating Radarmentioning
confidence: 95%
“…The advection of warm, dry air masses over the ice shelf during föhn winds is the likely cause of this surface melt distribution . A notable expression of this surface melt gradient is seen in the composition of the firn layer over the LCIS: the smallest amounts of firn air are found in the inlets in the western part of the LCIS (Holland et al, 2011;Ashmore et al, 2017). In Cainet Inlet (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations